Islam and Muslim history in South Asia - Robinson, Francis, 1944- (Oxford : Oxford University Press, 2000)
Essays address key themes in the history of the Muslims of South Asia: conversion to Islam; the impact of print; the emergence of this-worldly religion; the process of "secularization"; the relationship between religion and politics; and response to scholarly contributions to the field.
Includes bibliographical references and index.
Keywords: Islam -- South Asia -- History